Cisco 100-101 (ICND1) exam training - Dickinson, Greg.; Safari eBooks ([S.l.] : InfiniteSkills, 2013)
"In this Cisco 100-101 (ICND1) training course expert trainer Greg Dickinson prepares you for the Interconnecting Cisco Networking Devices Part 1 exam. The ICND1 exam gives you your CCENT (Cisco Certified Entry Networking Technician) certification, and is a required exam for achieving your full CCNA Routing and Switching certification. This tutorial covers the topics recommended by Cisco for the 100-101 (ICND1) exam. The Cisco 100-101 exam tests your knowledge of the network fundamentals required to install, operate, and troubleshoot a small branch office network. This video tutorial covers all of the recommended topics for this exam; operation of IP data networks, LAN switching technologies, IPv4 and IPv6, Routing Technologies, DHCP, NAT and ACLs, network device security and basic troubleshooting. Once you have completed this computer based video training course, you will have a thorough understanding of the concepts you need for passing the Cisco 100-101 (ICND1) exam. You will also be able to apply these concepts to building and managing a real-life client network."--Resource description page.
Title from resource description page (viewed Oct. 3, 2013).
Presenter, Greg Dickinson.
Keywords: Electronic data processing personnel -- Certification -- Study guides; Computer networks -- Examinations -- Study guides; Electronic books